Kontestasi Aktor dalam Pengelolaan Dana Desa - Putri, Rizky Trisna; Sjaf, Sofyan; Sri Wahyuni, Ekawati (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2021)
Village funds are sourced from the central government budget which is trasferred directly to the village government. This direct transfer takes place after Law No. 6/2014 or also known as The Village Law. This larger village fund can only be accessed by the village government if it follows the rules set by the central government so that the actor in the village will use their assets to accomodate their interests related to village fund management. This study aims to explain the contestation of actors in managing village funds in two villages. This study uses a qualitative method with a case study approach conducted in Suko Village, Probolinggo Regency and Sukadamai Village, Bogor Regency. The results of this study are the village head is the actor who plays the most role in managing village funds using symbolic asset which is the position of the village head. This asset is the strongest because it has legitimacy from the state to be able to make decisions related to the village fund management.